All-carbon-coated positive electrode material and preparation method and application thereof

通过在真空负压环境下使用水溶性高分子进行全碳包覆正极材料的制备,解决了富锂锰基正极材料的导电性差和循环稳定性低问题,实现了高效的电化学性能提升和安全 Improved performance and suitable for industrial production.

CN119153672AActive Publication Date: 2024-12-17TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411649316.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2024-12-17
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Lithium-rich manganese-based positive electrode materials have gas bloating problems caused by redox reactions, poor conductivity and low cycle stability under high voltages. The existing carbon coating methods are costly, not suitable for industrial production, and have limited results.

Method used

Using water-soluble polymers as carbon-coated precursors, the positive electrode material, water and water-soluble polymers are mixed in a vacuum negative pressure environment to form a gel-like mixture. After drying and carbonization, the total carbon-coated positive electrode material is achieved. Seamlessly coat the inside and the outside to build an electronic conductive network.

Benefits of technology

It significantly improves the conductivity and cyclic stability of the cathode material, inhibits oxygen precipitation and microcracks, is suitable for large-scale industrial production, and improves electrochemical performance and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153672A_ABST
    Figure CN119153672A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and provides an all-carbon-coated positive electrode material and a preparation method and application thereof, the preparation method comprises the following steps: in a vacuum negative pressure environment, mixing a positive electrode material, water and a water-soluble polymer to obtain a gel mixture, and then drying and carbonizing to obtain the all-carbon-coated positive electrode material. According to the invention, the water-soluble polymer is adopted as a carbon-coated precursor, and the water-soluble polymer completely coats the positive electrode material from inside to outside through a vacuum negative pressure method, so that the complete construction of an electronic conductive network from inside to outside can be completed after carbonization, and compared with the surface carbon coating of traditional micromolecule glucose and / or the mixing coating of a conductive carbon material, the preparation method has the advantages that the preparation process is simple, and the cost is low. The water-soluble polymer subjected to high-temperature carbonization can realize seamless coating of the positive electrode material, the conductivity of a material interface can be remarkably enhanced, and the problems of poor cycle performance, oxygen evolution and the like caused by untight coating or microcracks of a carbon material of the lithium-rich manganese-based positive electrode material are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a full-carbon coated positive electrode material and a preparation method and application thereof. Background Art

[0002] With the global energy crisis and the increasing awareness of environmental protection, new energy vehicles, as one of the important means of energy conservation and emission reduction, have developed rapidly. The popularity of new energy vehicles has promoted the innovation of power battery technology. Among them, the performance of positive electrode materials, as the core component of the battery, directly affects the energy density, safety and service life of the battery.

[0003] In recent years, with the rapid expansion of the new energy vehicle market and the rapid replacement of traditional fuel vehicles, the automotive market has increasingly higher requirements for high energy density, high safety and long life battery cathode materials. In this context, lithium-rich manganese-based cathode materials have attracted much attention due to their high energy density, environmental friendliness and low cost.

[0004] Lithium-rich manganese-based cathode materials are typical layered transition metal oxides that can provide additional capacity by utilizing the redox reaction of lattice oxygen anions at high voltages, thereby significantly improving the energy density of batteries. However, lithium-rich manganese-based cathode materials face the following key issues in commercial applications:

[0005] First, under high voltage, the lattice oxygen anions on the surface of the positive electrode material provide high capacity at high voltage, while their redox reaction releases oxygen, which will cause serious flatulence problems and pose a serious threat to the safety of the battery. Second, nickel-manganese metal oxides have poor electrical conductivity, which limits the power performance and cycle stability of the battery; third, during the charge and discharge process, the lithium-rich manganese-based positive electrode material will produce volume changes, which will lead to serious microcracks on the surface of the material. These microcracks will aggravate the penetration corrosion of the electrolyte and accelerate the occurrence of interface side reactions, thereby reducing the cycle stability of the material.

[0006] At present, there are some effective means in the field to improve the interfacial conductivity of lithium-rich manganese-based cathode materials, such as surface carbon coating (such as traditional glucose hydrothermal carbon coating, high-temperature pyrometallurgical coating, etc.) and / or mixed coating of highly conductive carbon materials (such as graphene, carbon nanotubes, etc.). Carbon-coated modified lithium-rich manganese-based cathode materials, especially surface carbon coating, can significantly improve the conductivity and inhibit the oxygen precipitation on the surface of the cathode material by reducing the contact between the cathode material interface and the electrolyte, becoming one of the research hotspots of high cycle stability and high rate lithium-rich manganese-based cathode materials. Compared with carbon-coated lithium-rich polycrystalline cathode materials, lithium-rich polycrystalline cathode materials without carbon coating have poor conductivity and poor interfacial stability, which makes lithium-rich polycrystalline materials show high oxygen release and poor cycle performance, which seriously hinders their practical application.

[0007] However, common methods of surface carbon coating, such as hydrothermal carbon coating, require long-term reaction under high pressure and high temperature conditions, which not only increases production costs, but also makes it difficult to achieve large-scale industrial production. In addition, since the molecular weight of the carbon source used, such as glucose, is small, surface coating can only be performed under strict hydrothermal conditions, and factors such as reaction temperature, pressure and time need to be precisely controlled, which undoubtedly increases the difficulty of process control. Therefore, it is not suitable for large-scale industrial low-cost production. Although high-temperature pyrometallurgical coating can avoid the pressure limitation of hydrothermal reaction, it requires higher temperature and easily leads to uneven surface conductive carbon coating, poor material conductivity consistency and uneven conductivity. Mixed coating of graphene and carbon nanotubes cannot achieve seamless connection between carbon materials and positive electrode materials. Compared with surface carbon coating, it has limited effect on improving material conductivity, and cannot effectively inhibit the precipitation of lattice oxygen at the interface of positive electrode materials, cannot inhibit microcracks generated during material circulation, and cannot prevent contact between positive electrode materials and electrolytes and the occurrence of side reactions.

[0008] Therefore, new technical solutions still need to be developed to solve or improve the problems of lithium-rich manganese-based positive electrode materials, or other positive electrode materials with microcracks, poor conductivity or loose carbon coating during actual service in a simple, easy and low-cost way, so as to comprehensively improve the electrochemical performance and stability of the positive electrode materials and promote the pace of commercialization. Summary of the invention

[0009] In view of the problems existing in the prior art, the purpose of the present invention is to provide a full carbon coated positive electrode material and a preparation method and use thereof, wherein the preparation method comprises mixing a positive electrode material, water and a water-soluble polymer under a vacuum negative pressure environment to obtain a gel-like mixture, and then drying and carbonizing to obtain a full carbon coated positive electrode material. The present invention uses a water-soluble polymer as a carbon coating precursor, and completes the full coating of the positive electrode material from the inside to the outside by the water-soluble polymer through a vacuum negative pressure method, so that after carbonization, the electronic conductive network can be fully constructed from the inside to the outside. Compared with the surface carbon coating of traditional small molecule glucose and / or the mixed coating of conductive carbon materials, the water-soluble polymer after high temperature carbonization in the present invention can achieve seamless coating of the positive electrode material, and can significantly enhance the conductive properties of the material interface, and solve the problems of poor cycle performance and oxygen precipitation caused by the loose coating of carbon materials and / or microcracks of lithium-rich manganese-based positive electrode materials.

[0010] To achieve this object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a fully carbon-coated positive electrode material, the preparation method comprising:

[0012] In a vacuum negative pressure environment, positive electrode material, water and water-soluble polymer are mixed to obtain a gel mixture; the obtained gel mixture is dried and carbonized in sequence to obtain a fully carbon-coated positive electrode material.

[0013] The present invention adopts a water-soluble polymer as a carbon coating precursor, and uses a vacuum negative pressure method to complete the full coating of the positive electrode material from the inside to the outside by the water-soluble polymer. In this process, due to the presence of a certain viscosity of the water-soluble polymer, the water-soluble polymer is not only adsorbed to the surface of the positive electrode material but also poured into the interior of the positive electrode material through the vacuum negative pressure, and gradually causes a gelation reaction, thereby obtaining a gel-like mixture, and then the gel-like mixture is dried and carbonized and heat-treated to complete the full construction of the electronic conductive network from the inside to the outside, so as to solve the problems of poor cycle performance, poor conductivity and oxygen precipitation of the positive electrode material caused by the loose contact between the traditional carbon material and the positive electrode material or the existence or occurrence of microcracks, and is particularly suitable for improving and enhancing the electrochemical properties and stability of lithium-rich manganese-based positive electrode materials.

[0014] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] As a preferred technical solution of the present invention, the vacuum degree of the vacuum negative pressure environment is -0.01~-0.13MPa, for example, -0.01MPa, -0.02MPa, -0.025MPa, -0.03MPa, -0.035MPa, -0.04MPa, -0.045MPa, -0.05MPa, -0.055MPa, -0.06MPa, -0.065MPa, -0.07MPa, -0.075MPa, -0.08MPa, -0.085MPa, -0.09MPa, -0.095MPa, -0.1MPa, -0.11MPa, -0.12MPa or -0.13MPa, etc.

[0016] Preferably, the method of achieving the vacuum negative pressure environment includes filtration.

[0017] Preferably, the vacuum degree of the vacuum negative pressure environment increases with the increase of the D50 particle size of the positive electrode material.

[0018] Preferably, the vacuum degree (MPa) of the vacuum negative pressure environment is used as the dependent variable, and the D50 particle size (μm) of the positive electrode material is used as the independent variable, and the following functional relationship y=-0.0051x-0.0029 is satisfied, and x and y satisfy the pure numerical calculation relationship in units of μm and MPa respectively.

[0019] That is, in the present invention, as the particle size of the positive electrode material particles increases, the vacuum degree of the most suitable vacuum negative pressure required presents a linear increasing trend and relationship within a certain range.

[0020] Preferably, the D50 particle size of the positive electrode material is 2.5-10.5 μm, for example, 2.5 μm, 3.5 μm, 4.5 μm, 5.5 μm, 6.5 μm, 7.5 μm, 8.5 μm, 9.5 μm or 10.5 μm.

[0021] As a preferred technical solution of the present invention, the positive electrode material includes a lithium-ion battery positive electrode active material and / or a sodium-ion battery positive electrode active material; the lithium-ion battery positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel manganese oxide, a ternary positive electrode material, a quaternary positive electrode material, lithium iron phosphate, lithium iron manganese phosphate or a lithium-rich manganese-based positive electrode material.

[0022] The preparation method described in the present invention is not necessarily targeted at a specific lithium-rich manganese-based positive electrode material. The preparation method is universal, that is, the positive electrode material can be selected as a series of other positive electrode materials with microcracks and poor conductivity, so as to achieve a full carbon coating effect from the inside to the outside of any positive electrode material, thereby improving the electrochemical performance of the material.

[0023] Preferably, the lithium-rich manganese-based positive electrode material includes polycrystalline or single crystal, including particles of small, medium and large sizes.

[0024] The present invention does not specifically limit the method for preparing the positive electrode material, which should be reasonably selected and adjusted according to needs and designs.

[0025] Illustratively, the method for preparing the lithium-rich manganese-based positive electrode material includes mixing a hydroxide precursor of the lithium-rich manganese-based positive electrode material with a lithium source and sintering the mixture to obtain the lithium-rich manganese-based positive electrode material.

[0026] Preferably, the lithium source comprises lithium carbonate.

[0027] Preferably, the amount of the lithium source and the hydroxide precursor of the lithium-rich manganese-based positive electrode material is controlled according to the ratio of the molar amount of the lithium element to the total molar amount of the transition metal element, which is 1:(1.5~1.6), for example, 1:1.5, 1:1.51, 1:1.52, 1:1.53, 1:1.54, 1:1.55, 1:1.56, 1:1.57, 1:1.58, 1:1.59 or 1:1.6, etc.

[0028] Preferably, the sintering is performed in an oxygen-containing atmosphere, which includes air.

[0029] Preferably, the sintering temperature is 800-1100°C, for example 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C or 1100°C, and the sintering time is 12-14h, for example 12h, 12.5h, 13h, 13.5h or 14h.

[0030] Preferably, the chemical formula of the hydroxide precursor of the lithium-rich manganese-based positive electrode material includes Mn x Co y Ni 1-x-y (OH)2 or Mn x Co y Ni 1-x-y CO3, wherein 0<x≤1, for example, x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc., 0≤y<1, for example, y can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8 or 0.9, etc., x+y≤1, for example, x+y can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc.

[0031] Preferably, the D50 particle size of the hydroxide precursor of the lithium-rich manganese-based positive electrode material is 2.5-10.5 μm, such as 2.5 μm, 3.5 μm, 4.5 μm, 5.5 μm, 6.5 μm, 7.5 μm, 8.5 μm, 9.5 μm or 10.5 μm, etc.; the specific surface area BET value is 10-40 m 2 / g, for example 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g or 40m 2 / g, etc.

[0032] Preferably, the method for preparing the hydroxide precursor of the lithium-rich manganese-based positive electrode material includes preparing a mixed metal salt solution of a transition metal, mixing it with a precipitant and a complexing agent, performing a precipitation reaction, and then performing aging, solid-liquid separation, drying and screening to obtain the hydroxide precursor of the lithium-rich manganese-based positive electrode material.

[0033] Preferably, the total metal ion concentration of the transition metal in the mixed metal salt solution of the transition metal is 120-140 g / L, for example, 120 g / L, 125 g / L, 130 g / L, 135 g / L or 140 g / L.

[0034] Preferably, the precipitant comprises an alkaline solution, and the concentration of the alkaline solution is 8-12 mol / L, for example, 8 mol / L, 8.5 mol / L, 9 mol / L, 9.5 mol / L, 10 mol / L, 10.5 mol / L, 11 mol / L, 11.5 mol / L or 12 mol / L, etc.

[0035] Preferably, the complexing agent includes aqueous ammonia, and the concentration of the aqueous ammonia is 8wt% to 25wt%, for example, 8wt%, 10wt%, 13wt%, 15wt%, 18wt%, 20wt%, 23wt% or 25wt%.

[0036] Preferably, the precipitation reaction is carried out under an inert atmosphere.

[0037] Preferably, the precipitation reaction includes first performing a nucleation reaction and then performing a growth reaction.

[0038] Preferably, the precipitation reaction temperature is 40-70°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C.

[0039] Preferably, the pH of the nucleation reaction is 10-12, for example, 10, 10.2, 10.4, 10.6, 10.8, 11, 11.2, 11.4, 11.6, 11.8 or 12.

[0040] Preferably, the nucleation reaction time is 1 to 2 hours, for example, 1 hour, 1.2 hours, 1.4 hours, 1.6 hours, 1.8 hours or 2 hours.

[0041] Preferably, the pH of the growth reaction is 9.5-12, for example, 9.5, 9.8, 10, 10.3, 10.5, 10.8, 11, 11.3, 11.5, 11.8 or 12, etc.

[0042] Preferably, the growth reaction time is 30 to 40 hours, for example, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours or 40 hours.

[0043] Preferably, the drying temperature is 100-120° C., for example, 100° C., 105° C., 110° C., 115° C. or 120° C., and the drying time is 8-16 h, for example, 8 h, 10 h, 12 h, 14 h or 16 h.

[0044] As a preferred technical solution of the present invention, the water-soluble polymer includes at least one of polyethylene glycol, polyacrylamide or polyacrylic acid, preferably polyethylene glycol.

[0045] It should be noted that water-soluble small molecules, such as glucose, cannot be adsorbed on the surface of the material by the negative pressure method of the present invention, and can only be surface coated by strict hydrothermal conditions. The carbon source of the present invention is a water-soluble polymer, which can be adsorbed on the surface of the material by vacuum negative pressure and penetrate into the interior of the positive electrode material for gelation. It can be carried out gently and quickly at room temperature, and is suitable for large-scale industrial expansion.

[0046] As a preferred technical solution of the present invention, the polyethylene glycol includes at least one of PEG600 to PEG10000, such as PEG600, PEG800, PEG1000, PEG1500, PEG2000, PEG4000, PEG6000, PEG8000 or PEG10000, etc.

[0047] As a preferred technical solution of the present invention, the solid-liquid ratio of the positive electrode material to the water is (0.2~2.5) mg:1mL, for example, 0.2mg:1mL, 0.5mg:1mL, 0.8mg:1mL, 1mg:1mL, 1.3mg:1mL, 1.5mg:1mL, 1.8mg:1mL, 2mg:1mL, 2.2mg:1mL or 2.5mg:1mL, etc.

[0048] As a preferred technical solution of the present invention, the mass ratio of the positive electrode material to the water-soluble polymer is (100~1000):1, for example, 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, 800:1, 900:1 or 1000:1, etc.

[0049] As a preferred technical solution of the present invention, the mixing method includes stirring, the stirring speed is 300~800rpm, for example, 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, etc., the stirring temperature is 15~35°C, for example, 15°C, 20°C, 25°C, 30°C or 35°C, etc., and the stirring time is 20~40min, for example, 20min, 25min, 30min, 35min or 40min, etc.

[0050] As a preferred technical solution of the present invention, the drying temperature is 150-200°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, and the drying time is 8-16h, for example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h or 16h, etc.

[0051] As a preferred technical solution of the present invention, the carbonization is carried out under an inert protective atmosphere, the carbonization temperature is 300-500°C, for example, 300°C, 330°C, 350°C, 380°C, 400°C, 420°C, 450°C, 480°C or 500°C, and the time is 2-3h, for example, 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, etc.

[0052] In the present invention, the water-soluble polymer is preferably carbonized at high temperature under an inert protective gas to achieve seamless carbon coating of the positive electrode material from the inside to the outside, which can effectively improve the conductivity of the positive electrode material, improve the cycle stability of the positive electrode material, prevent the contact between the interface of the positive electrode material and the electrolyte, and thus inhibit surface side reactions. In particular, it can effectively inhibit the interfacial oxygen precipitation of the lithium-rich manganese-based positive electrode material and promote the cyclic reversibility of lattice oxygen.

[0053] In a second aspect, a fully carbon-coated positive electrode material is obtained according to the preparation method described in the first aspect.

[0054] In a third aspect, a battery comprises the fully carbon-coated positive electrode material described in the second aspect.

[0055] Due to space limitations and to avoid redundancy, the present invention does not list all point values ​​within the above numerical range one by one, but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0056] Compared with the prior art solutions, the present invention has at least the following beneficial effects:

[0057] The preparation method of the present invention uses a water-soluble polymer to seamlessly coat the positive electrode material through vacuum negative pressure, which can fill the water-soluble polymer into the microcracks of the positive electrode material, and then achieve seamless carbon coating of the lithium-rich manganese-based positive electrode material from the inside to the outside by heating and carbonization, which can simultaneously solve the problems of poor cycle stability, interface side reactions and interface oxygen precipitation of lithium-rich manganese-based polycrystalline positive electrode materials. The present invention is very different from the existing carbon coating such as glucose hydrothermal method. The glucose hydrothermal method carbon coating reaction conditions are harsh, and a reactor needs to be used. The reaction conditions are dangerous and the coating duration is long. Compared with the mixed coating of graphene and carbon nanotubes, graphene and carbon nanotubes can only achieve mixed and uneven coverage, but cannot maximize the conductivity of the material, can only achieve the improvement of the conductivity of the composite material contact area, and cannot suppress the microcracks generated by the positive electrode material during the cycle. Although it can improve the conductivity of the material to a certain extent, the cycle stability of the positive electrode material cannot be guaranteed. Compared with traditional coated carbon materials, the present invention has obvious advantages: on the one hand, it can achieve gentle and rapid full carbon coating of the positive electrode material from the inside out under aqueous conditions, and the coated carbon source is cheap and easy to obtain; on the other hand, the obtained positive electrode material is not only optimized in conductivity, but also can inhibit the microcracks generated during the cycle process, thereby improving the material's cycle stability and rate discharge capability. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 is a schematic flow chart of a method for preparing a fully carbon-coated positive electrode material in Example 1;

[0059] Figure 2 The polycrystalline precursor Mn of the lithium-rich manganese-based material obtained in Example 1 0.65 Ni 0.35 FE-SEM test image of (OH)2;

[0060] Figure 3 is a FE-SEM image of the fully carbon-coated positive electrode material obtained in Example 1;

[0061] Figure 4 is the XRD pattern of the all-carbon coated positive electrode material obtained in Example 1;

[0062] Figure 5 This is a comparison chart of the cycle performance of the full carbon coated positive electrode material of Example 1 and the positive electrode material obtained in Comparative Example 1-1;

[0063] Figure 6 It is a Nyquist plot test diagram of the full carbon-coated positive electrode material of Example 1 and the positive electrode material obtained in Comparative Example 1-1;

[0064] Figure 7 It is a linear fitting diagram of the vacuum degree corresponding to the most suitable vacuum negative pressure of the positive electrode materials with different particle sizes in Example 1 and Example 4. DETAILED DESCRIPTION

[0065] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0066] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.

[0067] Example 1

[0068] This embodiment provides a method for preparing a fully carbon-coated positive electrode material. Figure 1 As shown, the preparation method comprises:

[0069] (1) Preparation of lithium-rich manganese-based polycrystalline cathode material precursor:

[0070] According to the lithium-rich manganese-based material polycrystalline precursor Mn 0.65 Ni 0.35 (OH)2, prepare a mixed metal salt solution of transition metals according to the molar ratio of Mn and Ni, control the total metal ion concentration to 130g / L, and prepare 10mol / L precipitant alkaline solution and 16wt% complexing agent ammonia water. First prepare the start-up base liquid in the reactor, and introduce nitrogen below the liquid surface to ensure an oxygen-free environment. Then the prepared mixed metal salt solution, complexing agent ammonia water and precipitant alkaline solution are respectively and simultaneously pumped into the reactor evenly and continuously for precipitation reaction; specifically, the temperature of the reaction system in the primary and secondary reactors is controlled at 55°C, the nucleation offline pH is controlled at 11.4, the nucleation reaction is first carried out for 1.5 hours, and after the nucleation is completed, the pump of the alkaline solution is turned off, so that the system pH drops sharply to 10, and the growth reaction is carried out. The growth cycle is 35 hours, and the reaction product is stopped after the D50 reaches the required particle size, and the precipitation reaction is terminated; then it is aged for 4.5 hours, and the aged product is filtered, washed with hot alkali and hot water until neutral, dried at 110°C for 12 hours, and then sieved with a sieve to obtain a lithium-rich manganese-based polycrystalline positive electrode material precursor. The particle size D50 of the precursor is 6μm, and the BET is 26m 2 / g;

[0071] Preparation of lithium-rich manganese-based polycrystalline positive electrode materials:

[0072] The lithium source lithium carbonate and the obtained lithium-rich manganese-based polycrystalline positive electrode material precursor Mn 0.65 Ni 0.35 (OH)2, according to the ratio of the molar amount of lithium element to the total molar amount of transition metals being 1:1.55), the mixture was sintered at 950°C for 13h in air to obtain a lithium-rich manganese-based polycrystalline positive electrode material with a particle size D50 of 6μm;

[0073] (2) Preparation of gel mixture by vacuum negative pressure method:

[0074] Measure 350mL of distilled water and add it to the cleaned suction flask, add a rotor to the suction flask, and place the suction flask on a magnetic stirrer. Weigh 300g of the obtained lithium-rich manganese-based polycrystalline positive electrode material and transfer it to the suction flask, then weigh 1.6g of water-soluble polymer polyethylene glycol as a carbon source and add it to the suction flask, turn on the stirring and filtration equipment, maintain the vacuum negative pressure state in the suction flask, and maintain the vacuum degree at -0.03MPa; stir at room temperature for 30min, with a speed of 650rpm. After the reaction is completed, filter the material in the suction flask to obtain a gel-like mixture; then filter the sample obtained by filtration

[0075] Preparation of all-carbon coated cathode materials by high temperature carbonization:

[0076] The obtained gel-like mixture was placed in an oven and dried at 180°C for 12 hours, and then the dried sample was placed in a tubular furnace, nitrogen was introduced, and carbonized at 400°C for 2.5 hours to obtain a fully carbon-coated positive electrode material.

[0077] Example 2

[0078] This embodiment provides a method for preparing a fully carbon-coated positive electrode material. In step (2) of the preparation method, different water-soluble polymers and / or different amounts of water-soluble polymers are used. The specific adjustments are shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0079] Example 3

[0080] This embodiment provides a method for preparing a fully carbon-coated positive electrode material. In step (2) of the preparation method, different vacuum degrees of negative pressure are used. The specific adjustment is shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0081] Example 4

[0082] This embodiment provides a method for preparing a fully carbon-coated positive electrode material. In the preparation method step (1), the preparation parameters are adjusted to obtain positive electrode materials with different particle sizes D50, and different vacuum degrees of negative pressure are used in step (2). The specific adjustments are shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0083] Example 5

[0084] This embodiment provides a method for preparing a fully carbon-coated positive electrode material. The preparation method uses a new positive electrode material such as NCM811, NCA, LMFP, etc. to replace the lithium-rich manganese-based positive electrode material obtained in step (1), and in step (2), the amount of polyethylene glycol and the vacuum degree of the vacuum negative pressure environment are adjusted accordingly. The specific adjustments are shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0085] Comparative Example 1

[0086] This comparative example provides a method for preparing a positive electrode material. In step (2) of the preparation method, a water-soluble small molecule such as glucose is used to replace the water-soluble polymer, or no carbon source is added. The specific adjustments are shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0087] Comparative Example 2

[0088] This comparative example provides a method for preparing a positive electrode material. In step (2) of the preparation method, no vacuum negative pressure state is applied. The specific adjustments are shown in Table 1. Except for the above, other conditions are exactly the same as those in Example 1.

[0089] Comparative Example 3

[0090] This comparative example provides a method for preparing a positive electrode material, wherein the preparation method uses a new positive electrode material NCM811, NCA, LMFP, etc. to replace the lithium-rich manganese-based positive electrode material obtained in step (1), and in step (2), a water-soluble small molecule such as glucose is used to replace the water-soluble polymer, or no carbon source is added, and / or, a vacuum negative pressure state is not applied in step (2). The specific adjustments are shown in Table 1. Except for the above, the other conditions are exactly the same as those in Example 1.

[0091]

[0092]

[0093] Characterization and Testing:

[0094] Ⅰ. Figure 2 The polycrystalline precursor Mn of the lithium-rich manganese-based material obtained in Example 1 0.65 Ni 0.35 FE-SEM test image of (OH)2. It can be seen from the figure that the obtained precursor has a polycrystalline morphology, the primary particles have good crystallinity, and the particle size is about 6μm.

[0095] Figure 3 This is the FE-SEM image of the fully carbon-coated positive electrode material obtained in Example 1. It can be seen from the image that the primary particle morphology of the fully carbon-coated positive electrode material formed by the vacuum negative pressure method and carbonization is well maintained, and the particle size is about 6μm.

[0096] Figure 4 This is the XRD diagram of the fully carbon-coated positive electrode material obtained in Example 1. It can be seen from the figure that the fully carbon coating does not affect the structure of the lithium-rich manganese-based positive electrode material.

[0097] Ⅱ. The positive electrode materials obtained in the examples and comparative examples were prepared into positive electrode sheets: the positive electrode materials, carbon black, binder PVDF and N-methylpyrrolidone were ultrasonically dispersed uniformly to form a slurry, which was then applied to an aluminum foil with a scraper; dried in a vacuum drying oven for 12 hours, and then the electrode sheets were rolled and cut into sheets.

[0098] The obtained positive electrode sheet is further assembled into a battery: the negative electrode shell, positive electrode shell, separator, obtained positive electrode sheet, negative electrode lithium sheet are assembled in a glove box, and the electrolyte used is lithium hexafluorophosphate. The assembled battery is left to stand for a period of time, installed on a battery testing system (voltage range: 2.3~4.55V) for constant current charge and discharge tests, and the impedance of the battery is tested using an electrochemical workstation.

[0099] Figure 5 It is a comparison chart of the cycle performance of the fully carbon-coated positive electrode material of Example 1 and the positive electrode material obtained in Comparative Example 1-1. It can be seen from the figure that at 2.3~4.55V, the fully carbon-coated positive electrode material obtained in Example 1 has a higher cycle retention rate, almost no capacity decay, and better cycle stability.

[0100] Table 1 shows the cycle performance data comparison of the remaining embodiments and comparative examples. It can be seen from the table that compared with Comparative Examples 1-1 to Comparative Examples 1-3, the cycle retention rates of the buckled electricity obtained by using polyethylene glycol, polyacrylic acid and polyacrylamide as carbon sources for full carbon coating in Example 1 and Example 2 are all improved, indicating that the water-soluble polymer carbon coating precursor can significantly improve the cycle stability of lithium-rich manganese-based positive electrode materials after high-temperature carbonization. In addition, it can be concluded from the results of Table 1 that compared with other polymer carbon sources, polyethylene glycol polymer has the greatest improvement in the cycle stability of the material and the best performance, which may be due to the rich alcohol hydroxyl groups of polyethylene glycol. The results of the comparative example using a small molecule carbon source are basically the same as those without a carbon source. The reason is that the small molecule carbon source itself has a small molecular weight and is water-soluble. It cannot be effectively adsorbed in the micropores of the positive electrode material, will flow out directly, and cannot be coated on the surface of the positive electrode material. Then, the vacuum negative pressure method using a small molecule carbon source is basically the same as the results without a carbon source, and there is no obvious effect.

[0101] Figure 6 This is a Nyquist plot test diagram of the full carbon coated positive electrode material of Example 1 and the positive electrode material obtained in Comparative Example 1-1, including the high frequency area on the left and the low frequency area on the right. The right intercept of the semicircle represents Rct, which is the charge transfer impedance of the sample. It can be seen from the figure that the Rct of the positive electrode material of Example 1 is reduced after full carbon coating, indicating that the full carbon coated positive electrode material of the present invention can effectively enhance the conductivity of the material and reduce the charge transfer resistance.

[0102] Example 3 and Example 4 of Table 1 show the effect of full carbon coating of positive electrode materials of different particle sizes under different vacuum degrees of vacuum negative pressure, and Comparative Example 2-1 shows the effect of carbon coating using water-soluble polymers under low vacuum (0MPa) and normal pressure without negative pressure. It can be seen from the table that too large or too small vacuum negative pressure is not conducive to the cycle stability of positive electrode materials. The possible reason is that when the vacuum negative pressure is too small, even in the low vacuum or normal pressure range, the water-soluble polymer cannot completely penetrate and achieve full coating of the positive electrode material from the inside to the outside, and when the vacuum negative pressure is too large, it may cause structural damage to the positive electrode material. Therefore, only when the vacuum negative pressure is within an appropriate range can the cycle stability of the positive electrode material be effectively improved.

[0103] Figure 7 It is a linear fitting diagram of the vacuum degree of the most suitable vacuum negative pressure corresponding to the positive electrode materials of different particle sizes in Example 1 and Example 4. It can be seen from the figure that with the increase of particle size, the required vacuum negative pressure shows a linear increasing trend within a certain range; after linear fitting analysis, the vacuum degree (MPa) of the vacuum negative pressure environment described in the present invention is used as the dependent variable, and the D50 particle size (μm) of the positive electrode material is used as the independent variable, and the following functional relationship y=-0.0051x-0.0029 is satisfied.

[0104] From the above, it can be seen that the present invention adopts water-soluble polymer as carbon coating precursor, and completes the full coating of the positive electrode material from the inside to the outside by the water-soluble polymer through the vacuum negative pressure method. In this process, due to the presence of a certain viscosity of the water-soluble polymer, it is not only adsorbed to the positive electrode material through the vacuum negative pressure, but also can be poured into the interior of the positive electrode material, and gradually causes a gelation reaction, thereby obtaining a gel-like mixture, and then the gel-like mixture is dried and heat-treated under carbonization to complete the full construction of the electronic conductive network from the inside to the outside, so as to solve the problems of poor cycle performance, poor conductivity and oxygen precipitation of the positive electrode material caused by the loose coating of the carbon material and the existence or occurrence of microcracks, and is particularly suitable for improving and enhancing the electrochemical properties and stability of lithium-rich manganese-based positive electrode materials.

[0105] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0106] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0107] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing a fully carbon-coated positive electrode material, characterized in that: include: In a vacuum negative pressure environment, positive electrode material, water and water-soluble polymer are mixed to obtain a gel mixture; the obtained gel mixture is dried and carbonized in sequence to obtain a fully carbon-coated positive electrode material.

2. The preparation method according to claim 1, characterized in that: The vacuum degree of the vacuum negative pressure environment is -0.01~-0.13MPa.

3. The preparation method according to claim 2, characterized in that: The vacuum degree of the vacuum negative pressure environment is used as the dependent variable, and the D50 particle size of the positive electrode material is used as the independent variable, and the following functional relationship y=-0.0051x-0.0029 is satisfied.

4. The preparation method according to claim 3, characterized in that: The D50 particle size of the positive electrode material is 2.5-10.5 μm.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The positive electrode material includes a lithium ion battery positive electrode active material and / or a sodium ion battery positive electrode active material; the lithium ion battery positive electrode active material includes at least one of lithium cobalt oxide, lithium nickel manganese oxide, a ternary positive electrode material, a quaternary positive electrode material, lithium iron phosphate, lithium iron manganese phosphate or a lithium-rich manganese-based positive electrode material.

6. The preparation method according to any one of claims 1 to 4, characterized in that: The water-soluble polymer includes at least one of polyethylene glycol, polyacrylamide or polyacrylic acid.

7. The preparation method according to any one of claims 1 to 4, characterized in that: The mass ratio of the positive electrode material to the water-soluble polymer is (100-1000):

1.

8. The preparation method according to any one of claims 1 to 4, characterized in that: The mixing method includes stirring, the stirring speed is 300-800 rpm, the stirring temperature is 15-35° C., and the stirring time is 20-40 min; The drying temperature is 150-200°C and the drying time is 8-16h; The carbonization is carried out under an inert protective atmosphere, the carbonization temperature is 300-500° C., and the time is 2-3 hours.

9. A fully carbon-coated positive electrode material, characterized in that: Obtained according to the preparation method according to any one of claims 1 to 8.

10. A battery, characterized in that: Contains the full carbon-coated positive electrode material according to claim 9.

Citation Information

Patent Citations

  • Preparation method of carbon cladding modified lithium manganate anode material

    CN102916178A

  • Preparation method of carbon nano tube filled / coated stannic oxide composite negative material

    CN103682348A

  • Carbon coated lithium ion battery electrode material and preparation method thereof

    CN108305992A

  • A preparation method of a double-carbon layer coated manganese oxide composite material

    CN109148859A

  • Carbon-coated ternary positive electrode material as well as preparation method and application thereof

    CN115818734A

Cited By

  • Sodium-ion battery positive electrode material and preparation method thereof, positive plate, sodium-ion battery and application of sodium-ion battery

    CN120497322A

  • NCM composite positive electrode material, preparation method thereof and battery

    CN120657108A